The pharmacokinetics and pharmacodynamics of dehydroepiandrosterone during use of an ethinylestradiol- and drospirenone-containing oral contraceptive. (December 2013) - Zimmerman, Yvette; Coelingh Bennink, Herjan J. T.; Wouters, Wout; Ebes, Frieda; Fauser, Bart C. J. M.
Abstract Background Combined oral contraceptives (COCs) reduce the levels of ovarian and adrenal androgens. Co-administration of dehydroepiandrosterone (DHEA) may normalise androgen levels during COC use. Objective To investigate the effect of the addition of DHEA to a COC on the pharmacokinetics (PK) and pharmacodynamics (PD) of DHEA and its sulphate (DHEA-S), and on levels of total and free testosterone (T). Methods In a prospective, randomised, double-blind, placebo-controlled, cross-over study involving 21 female volunteers, the PK and PD of DHEA and DHEA-S were investigated during the use of one cycle of a COC containing 30 μg ethinylestradiol (EE) and 3 mg drospirenone (DRSP) with and without daily co-administration of 50 mg DHEA. Results Treatment during one cycle with a COC containing EE and DRSP reduces the exposure to DHEA and DHEA-S by at least 20%. This loss of adrenal androgens can be fully compensated by daily oral co-administration of 50 mg DHEA. With DHEA co-administration total T levels rise significantly (1.44 nmol/L with DHEA vs. 0.82 nmol/L with placebo; p < 0.001). Free T levels decrease significantly with both DHEA and placebo treatment, but significantly less during co-administration of DHEA (6.34 pmol/L with DHEA vs. 3.96 pmol/L with placebo; p < 0.001). Conclusion By adding DHEA to a COC the loss of adrenal and ovarian androgens can be restored.